Use of Moina micrura (Kurz) as an Artemia substitute in the production of Macrobrachium rosenbergii (de Man) post-larvae - Alam, M.J.; Ang, K.J.; Cheah, S.H. (Elsevier Science, 1993)
Five different overnight feeding regimes of Artemia and Moina micrura, either solely or in combination, were tested for their effects in the production of Macrobrachium rosenbergii post-larvae. Significantly higher (P<0.05) production of 16.83±2.49 PL/1 with a corresponding survival rate of 56.09±8.30% was obtained for the larvae fed with a 50:50 combination of Artemia and Moina than that with Artemia alone (13.21±0.90 PL/1 with a corresponding survival rate of 44.20±2.99%). A diet of Moina alone resulted in the production of 9.81±1.38 PL/1 with a corresponding survival rate of 32.69±4.60% which was significantly lower than that for larvae fed the diet of Artemia alone. Howerver, Artemia alone did not show diet superiority over any of the combined diets. The maximum mortality and significantly lower development in larvae fed Moina were observed during the first half of the culture period. However, in the later period, mean larval stage development as well as the growth of post-larvae fed the Moina diet equalled that of larvae fed with other diets.